Exploring the Uses of OA Books via the JSTOR Platform - Montgomery, Lucy; Saunders, N.; Ozaygen, A.; Pinter, F. (Knowledge Unlatched Research, 2017)
This report is the outcome of research commissioned and funded by four presses. It engages with usage data made available by JSTOR relating to OA books in order to assist publishers in understanding how their OA content is being used; inform strategic decision making by individual presses in the future; and shed light on the potential for data relating to the uses of OA books to support the potential of open access books to reach wide audiences. More broadly this study will be of interest to librarians and research funders. It shows in depth the patterns of usage of OA books that are emerging, especially at the chapter level. Amongst the conclusions this study shows that more so than journals, the book business has been driven by intermediaries throughout its history. Even in the transition to ebooks intermediaries continue to be important in the widespread distribution of book content. Thus, having book content available through the full range of discovery outlets is critical to ensuring access to research communities. The high proportion of readers originating in North America and already on the JSTOR platform when they access the books examined in this study hints at the continued importance of multiple distribution pathways for OA books as a mechanism for ensuring that the key outputs of the Humanities and Social Sciences make their way beyond academia. Encouraging are the hints that users at institutions who might not otherwise afford access to publishers’ books (remembering that JSTOR customers subscribe to a wide range of different journal and book collections) are using OA books. These appear to include high schools and community colleges.